Detection of the ionospheric disturbances on GPS-TEC using Differential Rate Of TEC (DROT) algorithm - Karatay, Secil (Elsevier BV, 2020)
Abstract The solar, geomagnetic, gravitational and seismic activities can cause spatial and temporal (hourly, diurnal, seasonal and annual) variabilities of the ionosphere. Main observable ionospheric parameters such as Total Electron Content (TEC) can be used to quantify these. TEC is the total number of electrons on a ray path crossing the atmosphere. The network of world-wide Global Positioning System (GPS) receivers provide a cost-effective solution in estimating TEC over a significant proportion of global land mass. This study is focused on the analysis of the variations of ionosphere over a midlatitude region using GPS-TEC estimates for three Sun Spot Numbers (SSN) periods. The investigation is based on a fast and automatic variability detection algorithm, Differential Rate Of TEC (DROT). The algorithm is tested using literature data on disturbances generated by a geomagnetic activity, a Solar Flare, a Medium Scale Travelling Ionospheric Disturbance (MSTID), a Large Scale TID (LSTID) and an earthquake. Very good agreement with the results in the literature is found. DROT is applied to IONOLAB-TEC estimates from nine Turkish National Permanent GPS Network (TNPGN Active) stations over Turkey to detect the any wave-like oscillations, sudden disturbances and other irregularities during December, March, June, September months for 2010, 2011, 2012 years. It is observed that DROT algorithm is capable of detecting both small and large scale variability due to climatic, gravitational, geomagnetic and solar activities in all layers of ionosphere. The highest DROT values are observed in 2010 during winter months. In higher solar activity years of 2011 and 2012, DROT is able to indicate both seasonal variability and severe changes in ionosphere due to increased number of geomagnetic storms and local seismic activities.
Keywords: 13. Climate action